2015
DOI: 10.3389/fpls.2015.00891
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation and gene regulatory basis for the responses of asparagus beans to soil drought

Abstract: Asparagus bean (Vigna unguiculata ssp. sesquipedalis) is the Asian subspecies of cowpea, a drought-resistant legume crop native to Africa. In order to explore the genetic variation of drought responses in asparagus bean, we conducted multi-year phenotyping of drought resistance traits across the Chinese asparagus bean mini-core. The phenotypic distribution indicated that the ssp. sesquipedalis subgene pool has maintained high natural variation in drought responses despite known domestic bottleneck. Thirty-nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…The donor parent of these RILs, S35 and SP2417 was VPD sensitive, and it shows that donor parent could conserve soil moisture when midday VPD was high. Similar kind of experimental data was also obtained by Vadez et al (2015) in VPD sensitive and insensitive sorghum, mapping population parents of PRLT and H77 pearl millet and cowpea genotypes; Xu et al (2015) identified the genotypic variation in transpiration pattern during mid-day in vigna unguiculate species. The restriction in transpiration under high VPD allowed by partial stomata closure saves soil moisture at the early vegetative stage, which can increase moisture availability for reproductive stages under the rainfed condition and can enhance yield (Richards and Passioura 1989;Sinclair et al 2005).…”
Section: Discussionsupporting
confidence: 69%
“…The donor parent of these RILs, S35 and SP2417 was VPD sensitive, and it shows that donor parent could conserve soil moisture when midday VPD was high. Similar kind of experimental data was also obtained by Vadez et al (2015) in VPD sensitive and insensitive sorghum, mapping population parents of PRLT and H77 pearl millet and cowpea genotypes; Xu et al (2015) identified the genotypic variation in transpiration pattern during mid-day in vigna unguiculate species. The restriction in transpiration under high VPD allowed by partial stomata closure saves soil moisture at the early vegetative stage, which can increase moisture availability for reproductive stages under the rainfed condition and can enhance yield (Richards and Passioura 1989;Sinclair et al 2005).…”
Section: Discussionsupporting
confidence: 69%
“…Five quantitative trait loci related to drought and senescence physiology have been identified by studying the natural variation in local cowpea landraces, including the "stay green" phenotype (Muchero et al, 2009) (Muchero et al, 2010). Similar quantitative loci were also identified in asparagus bean (Xu et al, 2015). Whole plant physiology mechanisms therefore contribute to plant droughtstress adaptation.…”
Section: Rwc Variation and Transpiration In Cowpeamentioning
confidence: 97%
“…Studying 40 cowpea genotypes, Belko et al (2013) found that drought-sensitive genotypes had higher transpiration rates than drought-tolerant genotypes both in well-watered and vapour pressure deficit conditions (Belko et al, 2013). Natural variation in drought resistance in a related species, Vigna unguiculata sesquipedalis (asparagus bean), was also attributed to variation in transpiration rates in response to vapour pressure deficit and soil drought (Xu et al, 2015). An explanation for our results could be that transpiration physiology and other mechanisms might contribute to local adaptation.…”
Section: Rwc Variation and Transpiration In Cowpeamentioning
confidence: 99%
“…A custom Agilent microarray targeting 29 471 cowpea unigenes was transferred from a previous Roche NimbleGen cowpea microarray (Xu et al, 2015). Hybridizations were performed for long-pod pools and short-pod pools, each consisting of RNA from seven independent genotypes, in three replicates.…”
Section: Custom Cdna Microarray Construction Hybridization and Data mentioning
confidence: 99%
“…Details of the 14 genotypes used for pooling can be found in Table S1. Methods for RNA extraction, purification and quantification were as described in Xu et al (2015). All cDNA were labelled with the fluorescent dye Cy5-dCTP using cRNA amplification and labelling kit (CapitalBio, Beijing, China).…”
Section: Custom Cdna Microarray Construction Hybridization and Data mentioning
confidence: 99%